Die tschechischen Kontaktwoerter in der slovakischen Sprachpraxis und in der zeitgenoessischen Slovakistik - Gazdíková, Martina (Slavistische Beitraege, 2005)
The present work deals with the words in Slovak, which are considered "Czechisms" or "Czech contact words". She is thus addressing one of the most explosive topics in Slovak studies. She examines today's normative status of these words and their changes after the socio-political upheaval of the late 1980s and early 1990s. She then goes into the question of how the current normativistic appraisal or devaluation of these words is followed in the language practice. The empirical study focuses on the press language. The results of the sociolinguistic survey and exemplary excerpts from Internet forums illustrate the attitude of the Slovak speakers towards the words examined. The work also contains a historical overview of Slovak-Czech language contact and an index of approximately 1,800 lexical units.